A MULTI-OBJECTIVE APPROACH TO DEFINING EFFECTIVE POLICIES TO RELEASE THE STRUCTURAL CHANGE IN A COMPUTABLE GENERAL EQUILIBRIUM MODEL. - Laib, Walid (The journal of contemporary issues in business and government, 2024)
The aim of this article is to suggest changes to the economic policies of Algeria in order to address the structural imbalance in its economy. The goal is to shift from an economy that relies heavily on oil prices to a more stable and balanced production structure that promotes economic development. Using the CGEM model applied to the Algerian economy through GAMS, this article conducted a simulation of economic policies. The results of the simulation showed improvements in the production group and the demand for factors across all sectors, particularly agriculture and industry. Positive changes estimated at between 10% and 60% were recorded in all sectors. Moreover, this package of policies had a positive impact on exports outside the oil sector. Exports in the industrial sector increased positively by 128%, while those in the agricultural sector increased by 29%. These findings indicate that Algeria has enormous potential and comparative advantages in these sectors. If protected in the current period, they could emerge as strong sectors and contribute significantly to the country’s economic growth.